2016
DOI: 10.1371/journal.pone.0145774
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Wide Study of Copy Number Variation Associated with Nasopharyngeal Carcinoma in Malaysian Chinese Identifies CNVs at 11q14.3 and 6p21.3 as Candidate Loci

Abstract: BackgroundNasopharyngeal carcinoma (NPC) is a neoplasm of the epithelial lining of the nasopharynx. Despite various reports linking genomic variants to NPC predisposition, very few reports were done on copy number variations (CNV). CNV is an inherent structural variation that has been found to be involved in cancer predisposition.MethodsA discovery cohort of Malaysian Chinese descent (NPC patients, n = 140; Healthy controls, n = 256) were genotyped using Illumina® HumanOmniExpress BeadChip. PennCNV and cnvPart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
1
14
1
Order By: Relevance
“…In our current study, we did not observe the overall association between MICA*Del and NPC recently reported in a Taiwan Chinese population and a Malaysian Chinese cohort (Tse et al., ; Low et al., ). Further stratified analysis also failed to disclose any gender‐specific association between MICA*Del with NPC as reported in a Taiwan Chinese population (Tse et al., ).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In our current study, we did not observe the overall association between MICA*Del and NPC recently reported in a Taiwan Chinese population and a Malaysian Chinese cohort (Tse et al., ; Low et al., ). Further stratified analysis also failed to disclose any gender‐specific association between MICA*Del with NPC as reported in a Taiwan Chinese population (Tse et al., ).…”
Section: Discussioncontrasting
confidence: 98%
“…Recently, deletion of the MICA / HCP5 region was reported with an increased NPC risk among males in Taiwan Chinese population (Tse et al., ). Very recently, a suggestive association between deletion of the segment spanning MICA/HCP5/HCG26 genes and NPC was observed in a Malaysian Chinese cohort but not in a Malaysian Malay cohort (Low et al., ). However, MICA*Del did not exhibit any statistical association with NPC in an earlier study containing 218 NPC patients and 196 healthy controls from a southern Chinese Han population (Tian et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Such MIC variations are widely reported in worldwide populations such as Chinese [33,48,49,50], Indian [51], Iranian [52,53], Swedish [54], Finnish [55], Korean [56,57], Spanish [58], Bolivian [59], and Algerian [60]. …”
Section: Introductionmentioning
confidence: 86%
“…The association of MICA-129 with psoriasis (32) has been disproven in large GWAS cohorts (71). However, associations with NPC (33) and HCC (34) are supported by GWAS data pointing to the MICA gene region (4446). …”
Section: Mica-129met/val Disease Associations In View Of Biological Fmentioning
confidence: 98%
“…However, since the MICA-129Met/Val dimorphism is functional, it could also indicate that we need to better understand this function to predict its consequences in the pathophysiology of different diseases in various populations, which might be exposed to different interfering environmental factors. This assumption is supported by genome-wide association studies (GWAS), which have assigned disease risks for NPC (44), HCC (45, 46), cervical cancer (47, 48), and asthma (49) or advantages, such as HIV long-term non-progression (50) to the MICA gene region in an unbiased manner.…”
Section: Mica-129met/val Disease Association Studiesmentioning
confidence: 99%